Farm animal genetic resources in agro ecosystem of north east India - KADIRVEL, G; SINGH, L ANANDAKUMAR; RAHMAN, MOKIDUR; SINGH, N MANORANJAN (The Indian Journal of Animal Sciences, 2019)
North Eastern Region of India is the homeland of diverse animal genetic resources and representing a unique agro-ecosystem with integrated subsistence low input tribal production system where farm animals play an important role in improving the socio-economic status and livelihood of the people. The total livestock and poultry population of this region is about 70.13 million (6.85% of India) of which 92.76% is indigenous population. Among the 183 registered breeds of livestock and poultry in India, this region has 19 registered breeds which include two cattle, one buffalo, two goat, two sheep, four pig, two horse and ponies, one yak, four chicken and one duck breed. Besides many uncharacterized farm animal breeds/populations are reared by tribal farmers in the region, which are described as their local names. The review, enumerates the farm animal genetic resources of this region and their current status, descriptions, unique features, utility and their economic valuation and cultural importance as well as future conservation strategies. Precise and reliable estimation and evaluation of different economic and climate resilient traits of indigenous farm animal germplasm and their economic valuation, genetic characterization, documentation and registration is highly warranted. It has also suggested and proposed a model for the implementation of strict policy from central and state agencies to facilitate in situ conservation with active community participation and ex situ conservation through application of modern biotechnological tool, which is warranted to maintain the diversity of farm animals in north east region of India.